The baby boom and the stock market boom - Kyung-Mook Lim; David N. Weil (Brown University, Department of Economics, 2003)
This paper addresses two issues. The first is whether demographic change was plausibly responsible for the run-up in stock prices over the last decade, and whether the attempt by the baby boom cohort to cash out of its investments in the period 2010-30 might lead to an “asset meltdown.” The second issue is whether the rise in dependency that will accompany the retirement of the baby boom cohort calls for an increase in national saving. We analyze these issues using a forward-looking macro-demographic model, and show that they are related via the existence of installation costs for capital. If such costs are sufficiently large, then demographics do have the power to affect stock prices, but “saving for America's old age” is less optimal. However, conventional estimates of capital installation costs are not large enough to explain large stock price movements in response to actual demographic change.
Keywords: 330; Aktienmarkt; Börsenkurs; Bevölkerungsentwicklung; Sparen; USA